Research on The Use of Coordinating Conjunctions in The Jakarta Post’s Article ; The Unsung Heroes of Indonesia’s Economy - Abdul Harits Azizi Harits (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
ABSTRACTThis study aims to make a report on the use of coordinating conjunctions in an article in the Jakarta Post. This article is only written by Sheena Suparman and discuss about the Unsung Heroes of Indonesia’s Economy. The researcher found that there are four conjunctions used by the author of the article. The conjunction consists of For, And, But and Or. From the calculations carried out, the Author mostly used the conjunction “And” in his article. Followed by the conjunction “Or” which has been used twice while “For” and “But” were only used once. There is no sentence contained by Nor, Yet and So.